Pengembangan Media Scrapbook Berbasis Budaya Lokal untuk Meningkatkan Hasil Belajar IPAS pada Materi Keragaman Budaya - Kinanti, Putri; Akrom, Akrom; Meiliawati, Fithri (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The aim of this research is to develop local culture-based scrapbook media on cultural diversity material and to find out whether this media is feasible and can improve student learning outcomes. The method used in the research is R&D (Research and Development) with Thiagarajan's 4D model, which has four stages: define, design, develop, and disseminate. Data collection techniques used were observation, interviews, questionnaires, pre-test and post-test sheets. The product was tested in class IV with 18 students. Based on the research results, local culture-based scrapbook media has an average validation value from the three experts, namely 92% in the "Very Appropriate" category. The increase in student learning outcomes after using learning media shows the effectiveness of the media by obtaining an N-Gain value of 0.76 in the "High" category and an N-Gain percentage of 76.39% in the "Effective" category. Therefore, the use of local culture-based scrapbook media can improve student learning outcomes and is very suitable for use as a learning medium.